1987
DOI: 10.1063/1.338120
|View full text |Cite
|
Sign up to set email alerts
|

ArF excimer-laser-stimulated growth of polycrystalline GaAs thin films

Abstract: The growth of GaAs thin films by a laser photodecomposition process is reported. Ga(CH3)3 and As(CH3)3 mixtures are photolyzed above (100) Si and GaAs substrates by a 193-nm argon fluoride excimer laser beam directed normal to the substrate surface. Gas-phase products diffuse to, and stick on the surface where further laser irradiation leads to the formation of polycrystalline GaAs, with grain sizes between ∼20 and 2000 Å. Deposited films contain ∼1–3 at. % carbon, as determined by Auger electron spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The particular material used to construct these lamp envelopes did not permit the emission of the 185 nm radiation line. It has been demonstrated that the Hg-photosensitized decomposition of arsine proceeds as follows (lO) Hg + h~ (254.3 rim) --) Hg* [1] Hg* + AsH3--~ AsH2 + H + Hg [2] AsH2 ~ As + H2 [3] leading to the formation of As films. Here Hg* represents the excited Hg atom and hv represents the photon energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The particular material used to construct these lamp envelopes did not permit the emission of the 185 nm radiation line. It has been demonstrated that the Hg-photosensitized decomposition of arsine proceeds as follows (lO) Hg + h~ (254.3 rim) --) Hg* [1] Hg* + AsH3--~ AsH2 + H + Hg [2] AsH2 ~ As + H2 [3] leading to the formation of As films. Here Hg* represents the excited Hg atom and hv represents the photon energy.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main problems in the preparation of low resistivity p-type crystal is compensation caused by the residual donor-type impurities (2). The other problems are the so-called self-compensation (3) and the amphoteric behavior of acceptor-type impurities (4).…”
Section: Concl Usi Onsmentioning
confidence: 99%
See 1 more Smart Citation
“…193-nm photon has enough energy to break the first two Ga-CH3 bonds in TMGa, with ~52 kcal/mol excess energy, it is quite likely that reactions 22a,b occur rapidly sequentially, followed quickly by the absorption of a second photon in reaction 22d. 267 Since the second bond energy in TMAs is probably the weakest of the three (in analogy with other trimethylmetals), the energetics suggest that this sequence is probably also true for TMAs. Electronically excited Ga is formed during deposition, presumably due to reaction 22d, which fluoresces with an intensity varying quadratically with laser intensity.…”
Section: Iii-v Semiconductorsmentioning
confidence: 99%
“…Electronically excited Ga is formed during deposition, presumably due to reaction 22d, which fluoresces with an intensity varying quadratically with laser intensity. 267 In the absence of saturation, this implies a two-photon process with rapid thermal dissociation of DMGa by reaction 22b, and not a threephoton process, which would include photolysis of DMGa in reaction 22c. No statistical analysis of CH3 group removal from DMGa or DMAs has been performed, as has been done for the 193-nm photolysis of Fe(CO)5,115 to assess the importance of reaction 22b.…”
Section: Iii-v Semiconductorsmentioning
confidence: 99%